Hizketa arduragabearen tresnabidezko azterkerta akustikoa - Jauregi, Oroitz (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2004)
The article presents an experimental test of an acoustic study of spontaneous speech, where the durations of open and closed syllables have been measured, in order to conclude whether there is any significative difference between them. The results show that the differences in time between open and close syllables are significant. However, we should underline that the study has measured syllables in all contexts, and consequently, some variables that could condition the measures of the syllables have not been considered. On the other hand, the frequencies of open and close syllable structures have been calculated, showing that the great majority are open syllable structures. In this context, one of the aims of this study is to reclaim the neccesity of research of spontaneous speech, taking into account that it is the most usual speech style.